SELECTION OF OBJECTS TO SHOW TO FOREIGN TOURISTS - Kurbanova Sevara; Yusupova Mohlaroy Avazbek kizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: The purpose of the article is to analyse Selection of objects to show to foreign tourists. Along with globalization and the growth of emerging countries, international tourism has been increasing. Inbound tourism is of growing importance in many countries. Tourists' expectations when visiting a particular place are related to several features of the chosen destination: culture, architecture, gastronomy, infrastructure, landscape, events, shopping, etc. These features attract people to the destination and contribute to the overall experience of the trip.